Absent palmaris longus with hypoplastic flexor digitorum superficialis of the little finger: A rare case report (Indian Journal of Case Reports, 2021)
Anatomy of the tendons of the hand is of high clinical importance for plastic and reconstructive surgeons operating on hand and dealing with tendon injuries and hand reconstruction surgery. Among the variations in tendon Anatomy, variants of Flexor Digitorum Superficialis (FDS) and Palmaris longus (PL) are common. Here, we report an 18-year-old male patient, presenting to the emergency department with an alleged history of accidental glass cut injury over the volar aspect of the right wrist. On intraoperative exploration, his FDS of the little finger was hypoplastic and PL was found absent. Clinically, the absence of PL and Hypoplastic FDS to little finger can lead to problems in hand reconstructive surgeries. To the best of our knowledge, this case is the first of its kind where absent PL is associated with hypoplastic and thin FDS of the little finger.